Incidence of contralateral neurosensitive changes and persistent postoperative pain 6 months after mastectomy: A prospective, observational investigation - Masgoret, Paula (Medicine (Baltimore), 2020)
Mirror image sensory dysfunction (MISD) after breast surgery has not yet been studied. This prospective observational study aimed to determine the incidence of MISD, persistent postoperative pain (PPP) and mirror image pain (MIP) during 6 months after total unilateral mastectomy. Visual analogue scale (VAS), Neuropathic Pain Symptom Inventory (NPSI), Pain Catastrophizing Scale (PCS), Hospital Anxiety and Depression Scale (HADS), Life orientation test (LOT) and Quantitative Sensory Testing (QST) (in ipsi and contralateral breast, axilla and thigh) were recorded. VAS > 3 at 1, 3, and 6 postoperative months was considered PPP. Contralateral changes of QST at any time was considered indicative of MISD and spontaneous contralateral VAS ≥ 1 as MIP. Sixty-four patients were included. PPP at 1, 3 and 6 months was 18.8%, 56.2%, and 21.3%, respectively Ten patients presented MIP. MISD was detected in 79.7% patients in contralateral breast and 62.5% in contralateral axilla. Furthermore, changes in QST were present in 39.1% of patients in thigh. Electronic Von Frey (EVF) changes in both contralateral breast and axilla, and in thigh significantly diminished at all postoperative times. Changes of postoperative EVF ≥ 20% in contralateral breast were associated to higher VAS values. NPSI scores were significantly higher at all postoperative times. At 1 month, PCS, depression HADS subscale and LOT scores were significantly worse than all the other periods. MISD incidence was almost 80%, and 15.6% of patients showed spontaneous contralateral VAS ≥ 1. At 6 months 21.3% of patients manifested PPP. The worst alteration of factors related to PPP occurred at 1 postoperative month. Most consistent QST was EVF.